Pearl Millet (Pennisetum glaucum): Overview and Management - Yoana Newman; Ed Jennings; Joao Vendramini; Ann Blount (EDIS, 2010)
SS-AGR-337, a 6-page illustrated fact sheet by Yoana Newman, Ed Jennings, Joao Vendramini, and Ann Blount, describes this drought-resistant summer forage crop — plant description and adaptation, history and released cultivars, yield, nutritive value and antiequality factors, site selection, planting date and seeding rates, management, and utilization. Includes references. Published by the UF Department of Agronomy, September 2010.